2007
DOI: 10.2478/v10032-007-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Quality and Consumer Liking of Carrot Cultivars of Different Genotype

Abstract: Sensory Quality and Consumer Liking of Carrot Cultivars of Different GenotypeThe aim of this work was to determine sensory quality differentiation in various carrot cultivars of different genotype - with orange, purple and yellow storage roots. Consumer's test for liking carrots was performed in order to find consumer's preference level for carrots types and to determine the relationship between sensory profiles and consumer's attitude to carrots. An approach was also done to find correlations between descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…The valuation of the purple color of carrots is improved when adding information on the local origin and/or the organic method of production. This hypothesis builds on findings from Surles et al [12], Szymzcak et al [13], Shifferstein et al [16], and Martinez-Carrasco et al [31].…”
Section: Hypotheses (H2)supporting
confidence: 58%
See 2 more Smart Citations
“…The valuation of the purple color of carrots is improved when adding information on the local origin and/or the organic method of production. This hypothesis builds on findings from Surles et al [12], Szymzcak et al [13], Shifferstein et al [16], and Martinez-Carrasco et al [31].…”
Section: Hypotheses (H2)supporting
confidence: 58%
“…Surles et al [12] stated that orange carrots were the most preferred, while the purple carrots tended to be the least favorite. In the same way, Szymczak et al [13] reported higher scores for orange carrots than for yellow, white, and purple ones. Shifferstein et al [16] found that non-orange carrots (yellow, purple, and red) were perceived as less attractive and less familiar and that consumers were more likely to prepare and eat the orange carrots than the other ones.…”
Section: Literature Review Research Objective and Hypothesesmentioning
confidence: 69%
See 1 more Smart Citation
“…] and carrots [Szymczak et al . ] ). For some products (e.g., mangoes), including multiple stages of ripeness and storage times may also be necessary.…”
Section: Preparing For Lexicon Developmentmentioning
confidence: 99%
“…Selecting products for a fresh fruit or vegetable lexicon is complex because of the inherent and pervasive inconsistency in fresh fruits and vegetables. As much as possible, a wide range of cultivars should be selected for building fresh fruit and vegetable lexicons because sensory properties among cultivars may vary widely even within the same plant type (e.g., Muscadine grapes [Threlfall et al 2007], blackberries [Du et al 2010] and carrots [Szymczak et al 2007] ). For some products (e.g., mangoes), including multiple stages of ripeness and storage times may also be necessary.…”
Section: Samplesmentioning
confidence: 99%